Lessons for competing in the tough world of retail - Berman, Barry (FT Press Delivers elements., 2011)
This Element is an excerpt from Competing in Tough Times: Business Lessons from L.L. Bean, Trader Joe's, Costco, and Other World-Class Retailers (9780132459198) by Barry Berman. Available in print and digital formats. How retailers can gain deeper insights into their true position--and choose the right strategies for a marketplace that won't get any easier. According to Porter, the least-defensible competitive strategy is being "stuck in the middle." These retailers offer no long-term benefit in terms of either low prices or strong differentiation. The first part of addressing this is to recognize your true-- not ideal --marketplace positioning. Next, how can you determine whether a cost, value, or differentiation strategy is most suitable....